Assessment in the Hands of Primary School Mathematics Teachers: Four studies in China - Zhao, X.; Van den Heuvel-Panhuizen, M.; Veldhuis, M. (Lutheran University of Brazil, 2019)
In this paper, we describe four studies that have been done in the project Improving Classroom Assessment in China (ICA-C). The project was a sequel to the ICA project in the Netherlands. To shed light on the current situation of Chinese primary school mathematics teachers’ perception and practice of classroom assessment, we first did a review study based on teacher-written papers addressing classroom assessment. Then a large-scale questionnaire survey was conducted by means of which we could identify different assessment profiles of teachers. With the gained knowledge, two other studies were set up to explore the possibility for improving Chinese primary school mathematics teachers’ assessment activities, with a particular focus on using classroom assessment techniques in the domain of division and multiplication.
Keywords: classroom assessment; mathematics education; primary school; China